A chromium steel shot and production method
By employing specific chemical compositions and a dual cooling process, chromium steel shot resolves the conflict between toughness, strength, and wear resistance, achieving the preparation of high-performance chromium steel shot suitable for special environments requiring a combination of toughness, strength, and wear resistance.
Patent Information
- Application Number
- CN202411192784.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-08-28
AI Technical Summary
Existing high-carbon cast steel shot cannot achieve a balance between toughness, strength, and wear resistance, and therefore cannot meet the needs of special operating environments.
Chromium steel shot is prepared by smelting with specific chemical components and using water atomization. Combined with dual cooling treatment of CO/inert gas mixed gas air cooling quenching and water spray cooling quenching, nano-scale V(C,N) matrix grains are formed to ensure the uniformity of the bainite + martensite matrix structure.
It significantly improves the toughness, strength and wear resistance of chromium steel shot, and the product exhibits excellent overall wear resistance under high load conditions.
Smart Images

Figure CN119082602B_ABST
Abstract
Description
Technical field:
[0001] The invention belongs to the technical field of chrome steel shot production, and more specifically relates to a chrome steel shot and a production method thereof. Background technology:
[0002] At present, the high carbon cast steel shot or high carbon cast steel sand products used at home and abroad meet the standards of GB / T18838.3-2008 high carbon cast steel shot and sand, SFSA20-66 cast steel abrasive, SAE J827-1996 cast steel shot, SAE J1993-1996 high carbon cast steel sand, YB / T5149-1993 cast steel shot, YB / T5150-1993 cast steel sand, ISO11124-3-1993 high carbon cast steel shot and sand, JIS G5903-1975 cast steel shot and sand, and DIN 8201-2-1985 cast steel shot and sand.
[0003] The current high carbon cast steel shot technology is relatively mature. High carbon cast steel shot has the advantage of high strength, but the toughness, strength and wear resistance of steel are often contradictory. Due to the special use environment of steel shot, it is required that the steel shot must have toughness, strength and wear resistance.
[0004] Therefore, the reasonable selection of the chemical composition of steel and the use of reasonable refining, heat treatment and heat treatment processes to achieve better wear resistance, strength and toughness of the mold material have always been a hot topic in steel shot research. Summary of the invention:
[0005] In order to solve the above problems and overcome the shortcomings of the prior art, the present invention provides a chrome steel shot and a production method, which can effectively solve the special use environment of the steel shot, requiring the steel shot to have toughness, strength and wear resistance, while the toughness, strength and wear resistance of steel are often contradictory, making it impossible for the steel shot to have toughness, strength and wear resistance.
[0006] The specific technical solution of the present invention to solve the above technical problems is: chromium steel shot, characterized in that: the weight percentage of smelting is C: 0.15-0.18%, Cr: 0.020-0.040%, V: 0.00005-0.00015%, Ti: 0.003-0.006%, Si: 0.10-0.20%, Mn: 0.35-0.55%, P≤0.001%, S≤0.001%, and the balance is iron Fe.
[0007] A method for preparing chromium steel shot, characterized in that the components are used, and the steps include:
[0008] (1) adding the above-mentioned formula components into an electric furnace to melt into molten steel, and then using pure aluminum for deoxidation treatment,
[0009] (2) using water atomization to turn the molten steel into small droplets, which are then transformed into spherical droplets under the action of the surface tension of the molten steel and fall into a water pool. After cooling and solidification, semi-finished chrome steel shots are obtained, which are then dried in a rotary drying furnace;
[0010] (3) heating to 840° C. in a continuous rotating drum heat treatment furnace for 20-40 minutes, and then performing a first quenching treatment by air cooling quenching in a high-speed flowing atmosphere to obtain a semi-finished chromium steel shot that has been quenched once;
[0011] (4) The semi-finished chrome steel shot after the first quenching is tempered at 450-500° C. for 50-80 minutes; then the semi-finished chrome steel shot is quenched for the second time by spraying water mist, and finally placed in a furnace at 200-230° C. for 3-5 hours and then taken out of the furnace for air cooling to obtain the finished chrome steel shot.
[0012] Furthermore, the air-cooling component is a CO / inert gas mixture.
[0013] Furthermore, the volume ratio of the CO / inert gas mixed gas is (2-4):97, and the inert gas is nitrogen.
[0014] Furthermore, the water mist is composed of a mixture of water and carbon dioxide, and the volume mass ratio of carbon dioxide to water is 0.14-0.5%.
[0015] Furthermore, the hardness of the chrome steel shot reaches HRC47-52.
[0016] The beneficial effects of the present invention are:
[0017] The present invention adds vanadium and chromium to the formula to obtain chromium steel shots with superior toughness, strength and wear resistance compared to high carbon cast steel shots and alloy steel shots;
[0018] In the process of preparing chromium steel shot, the present invention adopts the CO / N2 mixed gas to carry out the first quenching treatment of air cooling quenching, so that the added vanadium can be evenly formed into nano-scale V (C, N) matrix grains under the action of CO / N2 and high temperature, further greatly improving the strength and toughness, and having better overall wear resistance.
[0019] In the preparation process of the present invention, a water mist is sprayed for the second cold quenching, and the water mist is a mixture of water and carbon dioxide, so that a water film and an air film are formed on the surface of the product to avoid oxygen interference, thereby ensuring a bainite + martensite matrix structure, and the core and the surface have the same strength and hardness. Carbon dioxide stabilizes the V (C, N) matrix grains to a certain extent, improves the strength and toughness, and has better overall wear resistance. Description of the drawings:
[0020] AttachedFigure 1 This is the transmission electron microscope TEM morphology of Example 2 of the present invention;
[0021] Attached Figure 2 It is the transmission electron microscope TEM morphology and diffraction pattern of the V(C,N) matrix grains in the bainite+martensite matrix structure of Example 2 of the present invention;
[0022] Attached Figure 3 This is the transmission electron microscope TEM morphology of comparative example 6 of the present invention, Specific implementation method:
[0023] In the description of the present invention, specific details are only for a full understanding of the embodiments of the present invention, but those skilled in the art should know that the implementation of the present invention is not limited to these details. In addition, well-known structures and functions are not described or shown in detail to avoid blurring the key points of the embodiments of the present invention. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0024] Specific implementation of the present invention:
[0025] In order to better understand the present invention, a specific embodiment is used for illustration. It is worth emphasizing that the effect of this embodiment is not substantially different from the various embodiments within the protection scope of the present invention, including the respective reagents and the content ratio of the reagents, and all of them can achieve the effects described in the present invention and solve the above-mentioned problems. Other combinations are not described here.
[0026] Example 1: Preparation method of chrome steel shot,
[0027] (1) The above-mentioned formula components are added into an electric furnace to be melted into molten steel, and then deoxidized by pure aluminum, wherein the formula components are as follows: C: 0.15%, Cr: 0.020%, V: 0.00005%, Ti: 0.003%, Si: 0.10%, Mn: 0.35%, P≤0.001%, S≤0.001%, and the balance is iron Fe.
[0028] (2) using water atomization to turn the molten steel into small droplets, which are then transformed into spherical droplets under the action of the surface tension of the molten steel and fall into a water pool. After cooling and solidification, semi-finished chrome steel shots are obtained, which are then dried in a rotary drying furnace;
[0029] (3) heating to 840° C. in a continuous rotating drum heat treatment furnace and keeping the temperature for 20 minutes, and then performing a first quenching treatment by air cooling quenching in a high-speed flowing atmosphere, wherein the air cooling component is a CO / inert gas mixed gas, wherein the volume ratio of the CO / inert gas mixed gas is 2:97, and the inert gas is nitrogen, to obtain a semi-finished chromium steel shot with a single cold quenching;
[0030] (4) The semi-finished chromium steel shot after the first quenching is tempered at 450° C. for 50 minutes; then the semi-finished chromium steel shot is quenched for the second time by spraying water mist, wherein the water mist is a mixture of water and carbon dioxide, and the volume mass ratio of carbon dioxide to water is 0.14%. Finally, the semi-finished chromium steel shot is placed in a furnace at 200° C. for 3 hours and then taken out of the furnace for air cooling to obtain the finished chromium steel shot.
[0031] The hardness of the processed product at 1 / 3 of the diameter reaches 48HRC. The Almen test piece was used to test the chrome steel shot with a specification of S550. The arc height of the test piece was 0.33mm. The ERVIN life value was measured by the 100% replacement method to be 4330 times.
[0032] Example 2: Preparation method of chrome steel shot,
[0033] (1) The above-mentioned formula components are added into an electric furnace to be melted into molten steel, and then deoxidized by pure aluminum, wherein the formula components are as follows: C: 0.16%, Cr: 0.030%, V: 0.00008%, Ti: 0.005%, Si: 0.15%, Mn: 0.40%, P≤0.001%, S≤0.001%, and the balance is iron Fe.
[0034] (2) using water atomization to turn the molten steel into small droplets, which are then transformed into spherical droplets under the action of the surface tension of the molten steel and fall into a water pool. After cooling and solidification, semi-finished chrome steel shots are obtained, which are then dried in a rotary drying furnace;
[0035] (3) heating to 840° C. in a continuous rotating drum heat treatment furnace and keeping the temperature for 30 minutes, and then performing a first quenching treatment by air cooling quenching in a high-speed flowing atmosphere, wherein the air cooling component is a CO / inert gas mixed gas, wherein the volume ratio of the CO / inert gas mixed gas is 3:97, and the inert gas is nitrogen, to obtain a semi-finished chrome steel shot that has been quenched once;
[0036] (4) The semi-finished chrome steel shot after the first quenching is tempered at 480° C. for 60 minutes; then the semi-finished chrome steel shot is quenched for the second time by spraying water mist, wherein the water mist is a mixture of water and carbon dioxide, and the volume mass ratio of carbon dioxide to water is 0.3%. Finally, the semi-finished chrome steel shot is placed in a furnace at 220° C. for 4 hours and then taken out of the furnace for air cooling to obtain the finished chrome steel shot.
[0037] The hardness of the processed product at 1 / 3 of the diameter reaches 52HRC. The Almen test piece was used to test the chrome steel shot with specification S550. The arc height of the test piece was 0.35mm. The ERVIN life value was measured by 100% replacement method and was 4490 times. The chrome steel shot with crushing resistance, impact resistance and toughness was obtained.
[0038] Example 3: Preparation method of chrome steel shot,
[0039] (1) The above-mentioned formula components are added into an electric furnace to be melted into molten steel, and then deoxidized by pure aluminum, wherein the formula components are as follows: C: 0.18%, Cr: 0.040%, V: 0.00015%, Ti: 0.006%, Si: 0.20%, Mn: 0.55%, P≤0.001%, S≤0.001%, and the balance is iron Fe.
[0040] (2) using water atomization to turn the molten steel into small droplets, which are then transformed into spherical droplets under the action of the surface tension of the molten steel and fall into a water pool. After cooling and solidification, semi-finished chrome steel shots are obtained, which are then dried in a rotary drying furnace;
[0041] (3) heating to 840° C. in a continuous rotating drum heat treatment furnace and keeping the temperature for 40 minutes, and then performing a first quenching treatment by air cooling quenching in a high-speed flowing atmosphere, wherein the air cooling component is a CO / inert gas mixed gas, wherein the volume ratio of the CO / inert gas mixed gas is 4:97, and the inert gas is nitrogen, to obtain a semi-finished chrome steel shot that has been quenched once;
[0042] (4) The semi-finished chrome steel shot after the first quenching is tempered at 500° C. for 80 minutes; then the semi-finished chrome steel shot is quenched for the second time by spraying water mist, wherein the water mist is a mixture of water and carbon dioxide, and the volume mass ratio of carbon dioxide to water is 0.5%. Finally, the semi-finished chrome steel shot is placed in a furnace at 230° C. for 5 hours and then taken out of the furnace for air cooling to obtain the finished chrome steel shot.
[0043] The hardness of the processed product at 1 / 3 of the diameter reaches 47HRC. The Almen test piece was used to test the chrome steel shot with specification S550. The arc height of the test piece was 0.34mm. The ERVIN life value was measured by 100% replacement method and was 4363 times. The chrome steel shot with crushing resistance, impact resistance and toughness was obtained.
[0044] In order to more intuitively demonstrate the process advantages of the present invention, the preparation method of chrome steel shot using the present invention is compared with the method using equivalent replacement in the same process.
[0045] Comparative Example 1:
[0046] The preparation method is the same as that of Example 2, except that: in the preparation process of this comparative example, one cold quenching is adopted, that is, the semi-finished chromium steel shot with one cold quenching is obtained, and finally the semi-finished chromium steel shot is placed in a furnace at 200-230°C for 3 hours and then taken out of the furnace for air cooling to obtain the finished chromium steel shot.
[0047] Comparative Example 2:
[0048] The preparation method is the same as that of Example 2, except that: in the preparation process of this comparative example, one cold quenching is adopted, that is, the semi-finished chrome steel shot is heated to 840°C in a continuous rotating drum heat treatment furnace and kept warm for 20-40 minutes, then cold quenched by spraying water mist, and finally placed in a furnace at 200-230°C and kept warm for 3 hours, and then taken out of the furnace and air-cooled to obtain the finished chrome steel shot.
[0049] Comparative Example 3:
[0050] The preparation method is the same as that in Example 2, except that in the preparation process of this comparative example, the air-cooling component is H2 / N2.
[0051] Comparative Example 4:
[0052] The preparation method is the same as that of Example 2, except that in the preparation process of this comparative example, the air-cooling component is CO2 / N2.
[0053] Comparative Example 5:
[0054] The preparation method is the same as that of Example 2, except that in the preparation process of this comparative example, the component of the water mist is water.
[0055] Comparative Example 6:
[0056] The preparation method is the same as that of Example 2, except that no metal vanadium is added during the preparation process of this comparative example.
[0057] According to the industry standards for the detection of hardness, arc height and life value, under the same detection level conditions, the hardness, arc height and life value of the finished chrome steel shots obtained in Comparative Examples 1-6 were tested, and the results are as follows:
[0058] Table 1: Performance of different embodiments and comparative examples in terms of hardness, arc height and lifespan
[0059] vanadium Air cooling quenching Water mist quenching Hardness / HRC Arc height Lifespan value Example 1 + <![CDATA[CO / N2]]> <![CDATA[H2O and CO2]]> 48 0.33 4330 Example 2 + <![CDATA[CO / N2]]> <![CDATA[H2O and CO2]]> 52 0.35 4490 Example 3 + <![CDATA[CO / N2]]> <![CDATA[H2O and CO2]]> 47 0.34 4363 Comparative Example 1 + <![CDATA[CO / N2]]> - 43 0.29 3850 Comparative Example 2 + - <![CDATA[H2O and CO2]]> 37 0.26 3340 Comparative Example 3 + <![CDATA[H2 / N2]]> <![CDATA[H2O and CO2]]> 38 0.27 3360 Comparative Example 4 + <![CDATA[CO2 / N2]]> <![CDATA[H2O and CO2]]> 36 0.26 3380 Comparative Example 5 + <![CDATA[CO / N2]]> <![CDATA[H2O]]> 41 0.28 3730 Comparative Example 6 - <![CDATA[CO / N2]]> <![CDATA[H2O and CO2]]> 35 0.25 3240
[0060] From the data analysis in Table 1, we can see that:
[0061] (1) In Examples 1-3, by configuring the content of the formula components and combining the two cold extraction processes, the hardness of the processed product at 1 / 3 of the diameter reached 52HRC; the Almen test piece was used to test the chrome steel shot with a specification of S550, and the arc height of the test piece was 0.35mm. The ERVIN life value was measured by the 100% replacement method to be 4490 times. The chrome steel shot with crushing resistance, impact resistance and toughness was obtained.
[0062] (2) Compared with Comparative Examples 1 and 2, the hardness, arc height and life value of Example 2 are significantly reduced.
[0063] Among them, both comparative examples 1 and 2 use one cold quenching, so it can be inferred that the two cold extraction processes have an effect of improving the hardness, arc height and life value of the chrome steel shot;
[0064] (3) Comparative Examples 1-2 and 3-4 are compared:
[0065] Although comparative example 3-4 was subjected to two cold extraction processes, the hardness, arc height value and life value were lower than those of comparative example 1. Therefore, the two cold extraction processes have an effect of improving the hardness, arc height and life value of the chrome steel shot, but not a dominant effect.
[0066] Among them, Comparative Example 3 also uses air-cooled quenching to perform the first quenching treatment. The air-cooled composition is H2 / N2. H2 and CO are both reducing gases, but the effects are far different. Therefore, in the two cold extraction processes, H2 is used as the air-cooled atmosphere, and the effect of CO / N2 on improving the hardness, arc height and life value of the chrome steel shot cannot be obtained. Comparative Example 3 is not much different from Comparative Example 4;
[0067] The principle may be: the first quenching treatment is carried out by CO / N2 air-cooled quenching. The CO atmosphere can promote the generation of CO-affinity crystal planes in the bainite + martensite matrix structure of the chromium steel shot, and nano-scale V (C, N) matrix grains are uniformly obtained on the CO-affinity crystal planes, which further greatly improves the strength and toughness, and has better overall wear resistance.
[0068] When the first quenching treatment is performed by H2 / N2 air-cooling quenching, although vanadium is added and C element is present, CO-affinity crystal planes cannot be produced due to the absence of CO atmosphere, and the conditions for uniformly obtaining nano-scale V(C,N) matrix grains on the CO-affinity crystal planes are not met.
[0069] (4) Compared with Comparative Example 1, although Comparative Example 5 also uses a water mist spraying method for the second cold quenching, since the water mist only contains water, Comparative Example 1 is better than Comparative Example 5 but the difference is not large.
[0070] The second cold quenching is carried out by spraying water mist, and the composition of the water mist is a mixture of water and carbon dioxide, forming a water film and an air film on the surface of the product to avoid oxygen interference and ensure the stability of the V(C,N) matrix grains evenly distributed in the bainite + martensite matrix structure. The core and the surface have the same strength and hardness. Carbon dioxide stabilizes the V(C,N) matrix grains to a certain extent, improves the strength and toughness, and has better overall wear resistance.
[0071] The principle may be: carbon dioxide can change the saturated vapor pressure of the atmosphere in the environment. Carbon dioxide stabilizes the V (C, N) matrix grains to a certain extent, improves the strength and toughness, and has better overall wear resistance.
[0072] (5) Example 2 and Comparative Example 6,
[0073] Although Comparative Example 6 uses a CO / inert gas mixture for the first quenching treatment by air cooling, and uses a water mist spray method for the second quenching, and the composition of the water mist is a mixture of water and carbon dioxide to form a water film and an air film on the surface of the product, but because no vanadium metal is added, V (C, N) matrix grains cannot be formed, and the strength and toughness cannot be fundamentally improved, and the overall wear resistance cannot be better.
[0074] By attaching Figure 1-3 By comparison, it can be seen that in Comparative Example 6, no vanadium was added. Figure 3 In the transmission electron microscope TEM morphology, there are no V (C, N) matrix grains, the overall structure grains are coarse and uneven, and the attached Figure 1 and attached Figure 2 In Example 2, uniform nanoscale V(C,N) matrix grains are obtained, and the center and surface of the bainite + martensite matrix structure are uniform. Carbon dioxide stabilizes the V(C,N) matrix grains to a certain extent, thereby improving the strength and toughness, and having better overall wear resistance.
[0075] In summary:
[0076] The present invention adds vanadium and chromium to the formula to obtain chromium steel shots with superior toughness, strength and wear resistance compared to high carbon cast steel shots and alloy steel shots;
[0077] In the preparation process of chromium steel shot, the present invention adopts the mixed gas of CO / inert gas to carry out the first quenching treatment of air cooling quenching, so that the added vanadium can obtain nano-scale V (C, N) matrix grains under the action of CO / inert gas and high temperature, further greatly improves the strength and toughness, and has better overall wear resistance.
[0078] In the preparation process of chromium steel shot, the present invention adopts a water mist spraying method to carry out the second cold quenching, and the water mist is a mixture of water and carbon dioxide, so as to form a water film and an air film on the surface of the product, avoid oxygen interference, ensure the bainite + martensite matrix structure, and the core and the surface have the same strength and hardness. The carbon dioxide stabilizes the V (C, N) matrix grains to a certain extent, improves the strength and toughness, and has better overall wear resistance.
Claims
1. A method for preparing chrome steel shot, characterized in that The weight percentage of the chromium steel shot is C: 0.15-0.18%, Cr: 0.020-0.040%, V: 0.00005-0.00015%, Ti: 0.003-0.006%, Si: 0.10-0.20%, Mn: 0.35-0.55%, P≤0.001%, S≤0.001%, and the balance is iron Fe; the preparation method comprises the following steps: (1) adding the above-mentioned formula components into an electric furnace to melt into molten steel, and then using pure aluminum for deoxidation treatment, (2) using water atomization to turn the molten steel into small droplets, which are then transformed into spherical droplets under the action of the surface tension of the molten steel and fall into a water pool. After cooling and solidification, semi-finished chrome steel shots are obtained, which are then dried in a rotary drying furnace; (3) heating to 840°C in a continuous rotating drum heat treatment furnace and keeping the temperature for 20-40 minutes, and then performing a first quenching treatment by air cooling quenching in a high-speed flowing atmosphere to obtain a semi-finished chromium steel shot with a single cold quenching, wherein the air cooling component is a CO / inert gas mixture; (4) The semi-finished chrome steel shot after the first quenching is tempered at 450-500° C. for 50-80 minutes; then the semi-finished chrome steel shot is quenched for the second time by spraying water mist, and finally placed in a furnace at 200-230° C. for 3-5 hours and then taken out of the furnace for air cooling to obtain the finished chrome steel shot.
2. The method for preparing chrome steel shot according to claim 1, characterized in that The volume ratio of the CO / inert gas mixed gas is (2-4):97, and the inert gas is nitrogen.
3. The method for preparing chrome steel shot according to claim 1, characterized in that The water mist is a mixture of water and carbon dioxide, and the volume mass ratio of carbon dioxide to water is 0.14-0.5%.
4. The method for preparing chrome steel shot according to any one of claims 1 to 3, characterized in that The hardness of the chrome steel shot reaches HRC47-52.
Citation Information
Patent Citations
Low bainite cast steel shots and surface strengthening device thereof
CN102121084A
Low carbon cast steel pellet
CN102851593A